Tackling causes and consequences of health inequalities : a practical guide - Matheson, James; Patterson, John, Dr; Neilson, Laura (CRC Press, 2020)
"Addressing health inequalities is a key focus for health and social care organizations, yet this is the first book to explore how best frontline health workers in areas of deprivation can address these problems. This book offers a concise but comprehensive overview of the key issues in health inequalities and how practically to address them"--